Kinerja Aspal Porus Termodifikasi Gilsonite: Penilaian Ketahanan Campuran Penilaian Ketahanan Campuran - Muhamad Anugerah Ramadhan; Nina Herlina; Sri Wanto (Universitas Pendidikan Nasional, 2026)
Porous asphalt is designed to improve surface drainage and driving safety, yet open-graded mixtures commonly suffer from limited stability and durability. This study investigates the effect of Gilsonite additive on porous asphalt performance using Pen 60/70 binder and local aggregates. The optimum asphalt content (OAC) was determined by integrating volumetric criteria (VIM), raveling resistance (Cantabro Loss), and binder drain-down stability (Asphalt Flow Down/AFD). The results indicate that increasing binder content decreases VIM and Cantabro Loss but markedly increases AFD; therefore, a balanced OAC of 5.58% was obtained with AFD of approximately 0.19%, which is below the maximum limit of 0.3%. At this OAC, Gilsonite contents of 0-3% consistently improved Marshall properties. Stability increased from 556.20 kg to 694.04 kg, or approximately 24.78%, while MQ increased from 149.03 to 208.24 kg/mm, or approximately 39.73%. Flow remained within 2-6 mm and VIM satisfied porous asphalt requirements at approximately 18.04-18.36%, indicating that the air-void structure was preserved. Immersion testing confirmed adequate moisture resistance, with IRS of 90.33-90.83% and decreasing degradation indicators (IDP and IDK) as Gilsonite content increased. The effectiveness of 3% Gilsonite is justified by the simultaneous improvement in stability, stiffness, and moisture durability without reducing porosity below the specification limit; therefore, this dosage represents the best formulation under the material conditions and mixture design adopted in this study.